2018
DOI: 10.1016/j.ecolind.2018.01.050
|View full text |Cite
|
Sign up to set email alerts
|

A mega-index for the Americas and its underlying sustainable development correlations

Abstract: Indicators and their composite indices have been embraced as development tools for guiding humanity toward a sustainable destination. In response, public and private organizations have generated hundreds of these metrics, making their application overwhelming to policymakers, planners, and scientists. Past reviews have revealed that a majority of common development indices have theoretical or quantitative shortcomings, supporting that there is no consensus regarding their theoretical basis, design, use, thresh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 61 publications
2
43
0
1
Order By: Relevance
“…Although these studies have identified the main anthropogenic and natural causes of salinity and the mechanisms behind them [29]. However, sustainable development is the holistic approach, including the three major divisions of economy, social and environment, so there is a huge requirement to excavate the indicators [30][31][32][33]. Therefore, scientific effort should not only be put into scientific indicator sources but should also be directed towards traditional information sources, since traditional knowledge may be holistic in outlook and adaptive by nature.…”
Section: Composite Risk Index For Irrigation Salinity Hazardmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these studies have identified the main anthropogenic and natural causes of salinity and the mechanisms behind them [29]. However, sustainable development is the holistic approach, including the three major divisions of economy, social and environment, so there is a huge requirement to excavate the indicators [30][31][32][33]. Therefore, scientific effort should not only be put into scientific indicator sources but should also be directed towards traditional information sources, since traditional knowledge may be holistic in outlook and adaptive by nature.…”
Section: Composite Risk Index For Irrigation Salinity Hazardmentioning
confidence: 99%
“…In the subjective weight assignment, the weights of relative importance of the parameters may be assigned based on the expert's preferences for the considered application, it has poor sense of interdependent criteria [36][37][38]. In the objective weight assignment, the weights of parameter's relative importance can be calculated by means of conventional statistical measures, it has poor sense of expert's preferences [33,34]. Therefore, it is rational to suppose that the combined use of subjective and objective weight assignment in soil salinity risk assessment is an interesting attempt.…”
Section: Composite Risk Index For Irrigation Salinity Hazardmentioning
confidence: 99%
See 1 more Smart Citation
“…The links between environmental conditions and living standards of the population of the region are shown in paper [9], and at the state level a similar topic is studied in paper [10]. Aspects of the most global importance are considered in the scientific works devoted to the methodology of measuring SEЕS sustainable development within the complex-valued development of the territory [11][12][13][14][15][16].…”
Section: Problem Statementmentioning
confidence: 99%
“…According to the 2030 Agenda for Sustainable Development, it clearly presents the relatively low level of correlation between the results obtained by individual European Union Member States on the subsequent levels of monitoring the implementation of EU strategy [10]. In the Americas, Shaker measured the three major divisions of sustainability (economic growth, social equity, environmental integrity), and ranked Belize best overall, followed by Guyana, Panama, Uruguay, and Canada; Barbados ranked worst, preceded by Haiti, Trinidad and Tobago, Mexico, and Cuba [11]. The BRICS ( Brazil, Russia, India, China and South Africa) group of countries is widely held to offer the prospect of a new approach to sustainable development, renewable energy and green economic growth in Africa, China and India have a significant existing and growing capacity to help move this forward [12].…”
Section: Introductionmentioning
confidence: 98%